Sudan I is a potential carcinogen for humans: evidence for its metabolic activation and detoxication by human recombinant cytochrome P450 1A1 and liver microsomes - Stiborová, Marie; Martínek, Václav; Rýdlová, Helena; Hodek, Petr; Frei, Eva (Cancer research, 2002)
1-Phenylazo-2-hydroxynaphthol (Sudan I, C.I. Solvent Yellow 14) is a liver and urinary bladder carcinogen in mammals. We compared the ability of hepatic microsomal samples from different species including human to metabolize Sudan I. Comparison between experimental animals and human cytochromes P450 (CYP) is essential for the extrapolation of animal carcinogenicity data to assess human health risk. Human microsomes generated the pattern of Sudan I metabolites reproducing that formed by hepatic microsomes of rats. Using hepatic microsomes of rats pretreated with specific CYP inducers, microsomes from Baculovirus-transfected insect cells expressing recombinant human CYP enzymes, purified CYP enzymes, and selective CYP inhibitors, we found that rat CYP1A1 and recombinant human CYP1A1 are the most efficient enzymes metabolizing Sudan I. Microsomes from livers (the target of Sudan I carcinogenicity) of different human donors were used to estimate whether authentic human CYPs oxidize Sudan I. Using Western blot analysis and NH(2)-terminal sequencing, we were able to detect and quantify CYP1A1 in human hepatic microsomes. The sequence of nine amino acids of the protein band cross-reacting with antirat CYP1A1 in human microsomes, LFPISMSAT, matched the sequence of human CYP1A1 perfectly (residues 2-10). CYP1A1 expression levels varied significantly among the different human microsomes (0.04-2.4 pmol/mg protein), and constituted <0.6% of the total hepatic CYP complement. All of the human hepatic microsomal samples oxidized Sudan I to C-hydroxymetabolites. Moreover, using the nuclease P1-enhanced version of the (32)P-postlabeling assay, we found that human microsomes were competent in activating Sudan I to form adducts with DNA. The role of specific CYP enzymes in the human hepatic microsomal metabolism was investigated by correlating the CYP-catalytic activities (or CYP contents) in each microsomal sample with the levels of individual metabolites and/or Sudan I-DNA adducts formed by the same microsomes, and by examining the effects of agents that can inhibit specific CYP in Sudan I metabolism. On the basis of these studies, we attribute most of Sudan I metabolism in human microsomes to CYP1A1, but participation of CYP3A4 cannot be ruled out. These results, the first report on the metabolism of Sudan I by human CYP enzymes, strongly suggest a carcinogenic potency of this rodent carcinogen for humans.
Keywords: Microsomes, Liver; prasata; Swine; Recombinant Proteins; Biotransformation; Inactivation, Metabolic; Cytochrome P-450 CYP1A1; metabolická inaktivace; naftoly; cytochrom P-450 CYP1A1; Naphthols; Swine, Miniature; králíci; oxidace-redukce; krysa rodu Rattus; rekombinantní proteiny; Animals; biotransformace; lidé; Carcinogens; karcinogeny; Humans; zvířata; Rats; Rabbits; Oxidation-Reduction; jaterní mikrozomy; miniaturní prasata